Mechanical and Cytocompatibility Evaluation of UHMWPE/PCL/Bioglass(®) Fibrous Composite for Acetabular Labrum Implant - Anindyajati, Adhi (Materials (Basel), 2019)
In this study, a fibrous composite was developed as synthetic graft for labral reconstruction treatment, comprised of ultra-high molecular weight polyethylene (UHMWPE) fabric, ultrafine fibre of polycaprolactone (PCL), and 45S5 Bioglass(®). This experiment aimed to examine the mechanical performance and cytocompatibility of the composite. Electrospinning and a slurry dipping technique were applied for composite fabrication. To assess the mechanical performance of UHMWPE, tensile cyclic loading test was carried out. Meanwhile, cytocompatibility of the composite on fibroblastic cells was examined through a viability assay, as well as SEM images to observe cell attachment and proliferation. The mechanical test showed that the UHMWPE fabric had a mean displacement of 1.038 mm after 600 cycles, approximately 4.5 times greater resistance compared to that of natural labrum, based on data obtained from literature. A viability assay demonstrated the predominant occupation of live cells on the material surface, suggesting that the composite was able to provide a viable environment for cell growth. Meanwhile, SEM images exhibited cell adhesion and the formation of cell colonies on the material surface. These results indicated that the UHMWPE/PCL/Bioglass(®) composite could be a promising material for labrum implants.